The Theory of Justice (Aristotle) Against Imperfect Collateral Binding Bad Debt Case at State-Owned Bank - Triana, Neny (JURNAL AKTA, 2025)
This study discusses the analysis theory of justice according to Aristotle regarding imperfect collateral binding in cases of bad debts at Indonesian state-owned banks. Credit is one of the main sources of income for banks, but the risk of bad debts is a significant challenge that requires protective measures, one of which is collateral. However, there are cases where collateral binding does not meet legal requirements, leaving problems related to justice for all parties. This research method is normative in qualitative descriptive analysis, exploring how Aristotle's theory of justice can be applied to evaluate this practice. The results show that Aristotle's theory of justice, which emphasizes proportion and recognition of rights, contributes to facilitating a fair relationship between banks and debtors. Increasing the use of collateral binding according to justice can contribute to creating a more fair and sustainable banking system in Indonesia.